An Analysis Of Religious And Cautionary Inscription And Sticker Texts In Nigeria - Reuben Oluwafemi Ikotun; Olusegun Adeniyi Faniran; Bolanle Tajudeen Opoola; Oluwatoyin Mary Olaiya (The Journal of Studies in Language, Culture and Society)
The high dominance of sticker texts, inscriptions and writings on vehicles or automobiles has attracted the attention of some researchers. However, none has discussed inscription and sticker texts with reference to social, political and economic vices that are prevalent in Nigeria. In this paper, we discuss religious and cautionary sticker texts, inscriptions and writings on vehicles or automobiles in relation to social, political and economic vices that are prevalent in Nigeria. Our data were drawn from the different major motor parks that constitute the nucleus of an assemblage of intra-city, inter-city and inter-regional vehicles of different brands as well as a variety of diverse messages conveyed by the vehicles across the south-western part of Nigeria. We also gathered some data from discarded automobiles which still carry faint and weather-beaten inscriptions on their mangled bodies at some mechanics’ workshops. We submit that despite the religious prayers that adorn the bodies of several automobiles, the incidence of moral decadence and all forms of criminal activities is alarmingly on the increase in Nigeria and that the religious prayers with reference to avoidable deaths on Nigerian roads seem unanswered in most cases in view of the daily reports of carnage on Nigerian roads. We argue further that beneath the aesthetic function of vehicle insignia is the profound communicative value inherent in the mobile emblems.